Public servant teachers’ evaluation during the internship period within the autonomous community of the Basque Country: towards the evaluation of the teaching role - Totoricagüena Barandica, Karmele (Avances en Supervisión Educativa, 2016)
The aim of this communication is to present the experience developed in the Basque Country regarding to the evaluation of the public servants in their internship period during the academic year 2015-16. The aim of this work is also to contribute the obtained conclusions to the teachers practice evaluation corpus. In that direction, and for the formalisation of the evaluation, new tools and specific materials had been prepared. The intervention carried out by the inspection had been done first informing and then interacting with the participants involved. From the developed experience can be determined that the classroom observation, the autoevaluation and the exchange/contrast of the observed practices done between the inspection and the evaluated participant should be the key elements to monitor the teaching role.